Taxonomic notes on Brazilian Encyclia (Orchidaceae: Laeliinae) - Bastos, Cláudia Araújo; Meneguzzo, Thiago E. C.; van Den Berg, Cássio (Phytotaxa, 2015)
In a recent taxonomic revision of the Brazilian species of Encyclia, we detected a need for several nomenclatural changes. Among the most important, we present here the clarification of several synonyms: Encyclia kundergraberi, E. santanae and E. zaslawskiana are synonymized under E. andrichii; E. ghillanyi under E. jenischiana; E. tarumana under E. mapuerae; E. edithiana and E. maderoi under E. replicate; and E. marxiana under E. viridiflora. Additionally, we designate lectotypes for E. ionosma, E. jenischiana and E. maderoi and neotypes for E. mapuerae and E. tarumana.